A log periodic dipole array antenna for UWB applications / Noor Fathiyah Abu Hassan - Abu Hassan, Noor Fathiyah (2010)
This paper presents the design of a microstrip antenna type log periodic dipole array (LPDA) with eight elements. The operating frequency range for this antenna is at Ultra Wide Band (UWB) from 3.1 GHz to 10.6 GHz. The antenna has been simulated using Computer Simulation Technology (CST) to obtain the response of return loss, VSWR, line impedance and radiation pattern. This LPDA antenna was fabricated using FR-4 substrate with a dielectric constant of 4.9 and thickness of 1.6mm. Both simulated and measured results are compared, analyzed and presented in this paper.